Growth Performance, Immune-Related and Antioxidant Genes Expression, and Gut Bacterial Abundance of Pacific White Leg Shrimp, Litopenaeus vannamei, Dietary Supplemented With Natural Astaxanthin - Mansour, Abdallah Tageldein; Ashour, Mohamed; Abbas, Eman M.; Alsaqufi, Ahmed Saud; Kelany, Mahmoud S.; El-Sawy, Mohamed A.; Sharawy, Zaki Z. (Frontiers in Physiology, 2022)
The current study examines the effect of dietary supplementation of ethanolic extract of Arthrospira platensis NIOF17/003, which is mainly natural astaxanthins (97.50%), on the growth performance, feed utilization, bacterial abundance, and immune-related and antioxidant gene expressions of the Pacific white leg shrimp, Litopenaeus vannamei. A total of 360 healthy L. vannamei postlarvae (0.19 ± 0.003 g) were divided into four groups (0, 2, 4, and 6 g natural astaxanthins/kg diet) each in three replicates, at an initial density of 30 PLs per tank (40 L capacity). The shrimp were fed the tested diets three times a day at a rate of 10% of their total body weight for 90 days. Diets supplemented with different astaxanthin levels significantly improved shrimp growth performance and feed conversion ratio compared to the control diet. No significant differences were observed in survival rates among all experimental groups. The immune-related genes (prophenoloxidase, lysozyme, beta-glucan binding protein, transglutaminase, and crustin) mRNA levels were significantly upregulated in groups fed with different concentrations of the natural astaxanthins in a dose-dependent manner. The prophenoloxidase gene is the highest immune-upregulated gene (14.71-fold change) in response to astaxanthin supplementation. The superoxide dismutase mRNA level was significantly increased with increasing dietary astaxanthin supplementation. In addition, increasing astaxanthin supplementation levels significantly reduced the count of heterotrophic bacteria and Vibrio spp. in the culture water and shrimp intestine. Overall, the current results concluded that diet supplementation with natural astaxanthin, extracted from Arthrospira platensis, enhanced the growth performance, immune response, and antioxidant status of L. vannamei.